Occupational fingertip eczema from acrylates in a manicurist - Denitza Zheleva; Razvigor Darlenski (Our Dermatology Online, 2015)
Occupational hand eczema due to acrylates present in the workplace is a disease frequently reported among dentists, printers, and fiberglass workers. Acrylate monomers are used in the production of a great variety of polymers, including nail cosmetics. Our case report demonstrates a rare clinical presentations of allergic contact dermatitis from acrylic nails. Our patient was working as a manicurist and the diagnostic analyses revealed sensitation to some of the (meth) acrylate compounds of her new nail cosmetics. Sculptured artificial acrylic and UV-hardened nails s are widely used in developed countries and they are gaining more and more popularity. We expect an increase in the number of cases of contact allergic dermatitis among manicurists and customers.